Transcriptional Modulation of Transport- and Metabolism-Associated Gene Clusters Leading to Utilization of Benzoate in Preference to Glucose in Pseudomonas putida CSV86 - Choudhary, Alpa (Appl Environ Microbiol, 2017)
The effective elimination of xenobiotic pollutants from the environment can be achieved by efficient degradation by microorganisms even in the presence of sugars or organic acids. Soil isolate Pseudomonas putida CSV86 displays a unique ability to utilize aromatic compounds prior to glucose. The draft genome and transcription analyses revealed that glucose uptake and benzoate transport and metabolism genes are clustered at the glc and ben loci, respectively, as two distinct operons. When grown on glucose plus benzoate, CSV86 displayed significantly higher expression of the ben locus in the first log phase and of the glc locus in the second log phase. Kinetics of substrate uptake and metabolism matched the transcription profiles. The inability of succinate to suppress benzoate transport and metabolism resulted in coutilization of succinate and benzoate. When challenged with succinate or benzoate, glucose-grown cells showed rapid reduction in glc locus transcription, glucose transport, and metabolic activity, with succinate being more effective at the functional level. Benzoate and succinate failed to interact with or inhibit the activities of glucose transport components or metabolic enzymes. The data suggest that succinate and benzoate suppress glucose transport and metabolism at the transcription level, enabling P. putida CSV86 to preferentially metabolize benzoate. This strain thus has the potential to be an ideal host to engineer diverse metabolic pathways for efficient bioremediation. IMPORTANCE Pseudomonas strains play an important role in carbon cycling in the environment and display a hierarchy in carbon utilization: organic acids first, followed by glucose, and aromatic substrates last. This limits their exploitation for bioremediation. This study demonstrates the substrate-dependent modulation of ben and glc operons in Pseudomonas putida CSV86, wherein benzoate suppresses glucose transport and metabolism at the transcription level, leading to preferential utilization of benzoate over glucose. Interestingly, succinate and benzoate are cometabolized. These properties are unique to this strain compared to other pseudomonads and open up avenues to unravel novel regulatory processes. Strain CSV86 can serve as an ideal host to engineer and facilitate efficient removal of recalcitrant pollutants even in the presence of simpler carbon sources.